Teachers’ Perspective and The Effectiveness on Improving Speaking Skills Through CoComelon Video - Dharistio, Luthfan; Anwar, Khoirul; Rochmah, Noviatul (JOLIES : Journal of Linguistic and English Studies, 2026)
This study examines teachers' perspectives and evaluates the effectiveness of using CoComelon videos as instructional media to enhance students' English speaking skills. The research was conducted with English teachers and fifth-grade students at Anubanloei School, Thailand. The research adopted a mixed-methods approach utilizing a pre-experimental design. A combination of t-tests and thematic analysis was employed to analyze the data. The instruments used included pre-tests, post-tests, questionnaires, and in-depth interviews for data collection. The findings demonstrate a significant improvement in students' speaking skills, particularly pronunciation, vocabulary, fluency, and comprehension, following the integration of Cocomelon videos as a teaching medium. Teachers reported that students exhibit greater engagement, increased motivation, and improved comprehension when exposed to visually appealing and age-appropriate video content compared to traditional media. Despite occasional technical difficulties, the study highlights the effectiveness of integrating multimedia into language teaching and the positive role of technology in fostering active, engaging, and enjoyable learning environments.